2020
DOI: 10.1051/meca/2020083
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-dynamical modelisation of the degradation of a ball bearing in variables use conditions

Abstract: Many sources of heat can emanate from the operation of a rotating machine, and one of which is the friction among the different parts of the ball bearings. Over time, these frictions may lead to a tearing of matter of the rings or on the rolling elements that cause some type of degradation by flaking. Flaking, in turn, produces a repetitive shock as a new source of thermal energy. This work proposes a physical model for the study of the thermal heating of a ball bearing during operation. The resolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Belmiloud et al [18] studied the heat generated by friction in the running process of bearings, and found that as the speed increased, the temperature at the location of the defective ball increased more significantly compared to that of the normal ball. Wang L et al [19] obtained the bearing vibration properties with the influence of temperature by establishing a bearing thermomechanical coupling model and calculating the bearing thermal deformation under different operating speeds. From the above research, the bearing thermal deformation plays a significant role in bearing stiffness and vibration characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Belmiloud et al [18] studied the heat generated by friction in the running process of bearings, and found that as the speed increased, the temperature at the location of the defective ball increased more significantly compared to that of the normal ball. Wang L et al [19] obtained the bearing vibration properties with the influence of temperature by establishing a bearing thermomechanical coupling model and calculating the bearing thermal deformation under different operating speeds. From the above research, the bearing thermal deformation plays a significant role in bearing stiffness and vibration characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the finite element method, the thermal network method has advantages such as mesh density, settable nodes and easy setting of boundary conditions [ 25 ]. Some scholars have studied the number of nodes [ 26 ], the distribution form [ 27 ] and the boundary setting method [ 28 ] of the network, and further developed the transient thermal network model of the bearing system [ 29 ], which can forecast the bearing temperature more precisely than the original steady state model.…”
Section: Introductionmentioning
confidence: 99%